2013
DOI: 10.1258/ar.2012.120541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Single-Shot and Readout-Segmented Diffusion-Weighted Imaging in Stroke Patients at 3 T

Abstract: Substantial image quality improvements are possible with readout-segmented vs. single-shot EPI - the current clinical standard for DWI - regardless of field strength (1.5 or 3 T). This results in improved image quality secondary to greater real spatial resolution and reduced artifacts from susceptibility in MR imaging of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
(30 reference statements)
9
31
0
Order By: Relevance
“…Regarding the qualitative assessment, rs-EPI was found to be superior to ss-EPI in overall image quality, anatomical structure distinction, and conspicuity of the lesions. It is consistent with previously published studies (8, 14, 15, 16). In a recent study investigating the diagnostic value of rs-EPI in 47 patients of breast lesions, rs-EPI provided higher image quality and lesion conspicuity compared to ss-EPI (14).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Regarding the qualitative assessment, rs-EPI was found to be superior to ss-EPI in overall image quality, anatomical structure distinction, and conspicuity of the lesions. It is consistent with previously published studies (8, 14, 15, 16). In a recent study investigating the diagnostic value of rs-EPI in 47 patients of breast lesions, rs-EPI provided higher image quality and lesion conspicuity compared to ss-EPI (14).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with those of Morelli et al (16), who compared ss-EPI and rs-EPI in the brain MRI. However, SNR in rs-EPI was lower than that in ss-EPI in the other studies (8, 14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggested that although the SNRs of the rs-EPI images were decreased, they exhibited less severe susceptibility artifacts and distortion, resulting in improved visualization of the target lesions. Morelli, 11 Holdsworth, 12 and Naganawa and associates 13 reported the acquisition of high resolution diffusion images and improved visualization of the brainstem and cranial nerves during studies of the head in patients with stroke. Whereas Naganawa's group set the voxel size on rs-EPI at 0.5 © 0.6 © 4 mm, we set it at 1.0 © 1.0 © 1.5 mm, which reduced the slice thickness, during imaging using a matrix size of 226 © 226 because the target lesions were cholesteatomas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Porter and Heidemann 19 implemented a readout-segmented EPI with parallel imaging, which combined reduced susceptibility artifact with superior motion correction while only marginally increasing the scan time. 20 …”
Section: Magnetization Transfer Contrastmentioning
confidence: 99%